O GÊNERO EPIDÍTICO NO DISCURSO JESUÍTICO: história e exemplos nas crônicas do maranhão-XVII e XVIII - Carvalho, Roberta Lobão; Silveira, Arlindyane Santos da (Outros Tempos: Pesquisa em Foco - História, 2012)
In this paper, we aim to demonstrate that the narrative of the Jesuit Maranhão seventeenth and eighteenth centuries, as in other parts of the Portuguese Empire, strove to create exemplary and paradigmatic figures, rewriting the biography of these personages and strengthening their political status and religious in the region. Therefore we will examine the lives of priests Luís Figueira, founder of Mission in the State, João de Souto Maior, "paragon of virtue and perseverance," and the mission of Father Francisco Veloso, who, according to the chroniclers, "descended alone Tupinambá by divine grace. "In these diverse and retold narratives are the fundamentals of writing Ignatian, which reflects directly on your ideal of history, that is uplifting and therefore exemplary. The reports will be examined from three chronicles: the first is the  Crônica dos Padres da Companhia de Jesus no Estado do Maranhão (1627-1698), written by Father John Philip Bettendorff, the second is entitled Crônica da Companhia de Jesus da Missão do Maranhão, [1720], father Domingos de Araujo. The last is the chronic priest José de Moraes,  História da Companhia de Jesus no Antigo Estado do Maranhão e Pará, 1759.